Evaluating the Impact of Educational Interventions on Medication Adherence Among Glaucoma Patients in Kazakhstan: A Public Health Perspective - Taushanova, Maiya; Yermukhanova, Lyudmila; Tazhbenova, Saule; Aitmaganbet, Perizat; Muratov, Yesset; Irmekbayev, Ruslan; Balday, Issenova; Abilkassym, Dana (Bangladesh Journal of Medical Science, 2024)
Objective: Glaucoma, a prevalent eye condition stemming from optic neuropathy, can cause irreversible blindness if not treated. Lack of adherence to medical treatments for glaucoma often results in severe outcomes, including ongoing vision loss and eventual blindness. The aim of this study was to assess treatment adherence among glaucoma patients who attended the Glaucoma School at urban clinics in Aktobe, Kazakhstan. Material and Methods: A cross-sectional study was conducted involving 183 glaucoma patients who sequentially underwent training at Glaucoma Schools in Aktobe, Republic of Kazakhstan. Data on adherence to glaucoma treatment were collected using the standardized Morisky Medication Adherence Scale-8 (MMAS-8) through a questionnaire. Analysis was performed using the statistical software SPSS (version 27.0.0.0, IBM Corporation, USA) and GraphPad Prism 9.5.1.733. A p-value of <0.05 was considered statistically significant. The study proposal was approved by the local bioethics committee of the West Kazakhstan Marat Ospanov Medical University. Results: The study has identified a significant improvement in medication adherence among glaucoma patients, with reductions in the frequency of forgetting to administer eye drops—from daily forgetfulness (p < 0.001) to specific situations like travel (p = 0.001). There was a notable increase in the proportion of patients properly administering their eye drops the day before, with a significant rise from 63.9% to 72.1% (p < 0.001). Overall, the median adherence score improved significantly from 4,75 to 5,5 (p < 0.001) and there was a minor, non-significant shift towards higher adherence categories after the educational intervention (p = 0.166). Socioeconomic factors such as education and income levels significantly influenced adherence before the intervention, with higher levels associated with better adherence (p < 0.001 for education, p = 0.020 for income). Conclusions: The study underscores that while educational interventions at the glaucoma school have shown improvements, adherence levels continue to be low, underscoring the necessity for sustained endeavors to bolster treatment adherence. Initiatives such as lectures, workshops, and seminars have proven successful in heightening awareness and garnering community support, thus positively affecting adherence. Socioeconomic factors exert a notable influence on adherence, indicating the importance of integrating social support into medical programs to assist economically disadvantaged groups. Limitations of the study include its brief duration and narrow geographical scope, potentially limiting the generalizability of the findings.Nonetheless, it provides valuable insights into managing glaucoma and underscores the necessity for continued research to refine educational and support strategies for glaucoma patients. Bangladesh Journal of Medical Science Vol. 23 No. 03 July’24 Page : 787-796